Physical, Chemical and Sensory Properties of Liquid Palm Sugar With The Addition of Canvas Seeds and Coconut Oil: Liquid Palm Sugar - Santika, Rika; Marniza, Marniza; Gusriani, Ika; Syafnil, Syafnil (Jurnal Bio-Geo Material Dan Energi, 2023)
The common form of palm sugar is usually in solid form and needs to be dissolved before use. To facilitate utilization, palm sugar is processed into liquid palm sugar. One of the issues encountered during the production of liquid palm sugar is the formation of foam, which can decrease the quality of the liquid palm sugar. Therefore, measures are needed to anticipate foam formation, including the addition of candlenut seeds and coconut oil. This study aims to determine the influence of the addition of candlenut seeds and coconut oil on the physical and chemical characteristics of liquid palm sugar, identify the optimal levels of candlenut seeds and coconut oil that meet the national standard (SNI) for liquid palm sugar, and produce a liquid palm sugar product preferred by consumers. The research employed a Randomized Complete Block Design (RCBD) with a single factor and six treatment levels of candlenut seeds and coconut oil (0%, 0.1%, 0.3%, 0.5%, 0.7%, and 0.9%). Data analysis was conducted using Analysis of Variance (ANOVA). Based on the research results, the addition of candlenut seeds and coconut oil significantly influenced the viscosity of liquid palm sugar but had no significant effect on its color and moisture content. The addition of candlenut seeds and coconut oil had a significant impact on the chemical quality of liquid palm sugar, affecting ash content and total insoluble solids but showing no significant effect on pH and total dissolved solids. The treatment with 0%, 0.1%, and 0.3% additions of candlenut seeds and coconut oil met the quality requirements for moisture content, while the ash content in the 0%, 0.1%, and 0.3% treatments also complied with the standards. The addition of 0.9% candlenut seeds and coconut oil resulted in liquid palm sugar that met both SNI standards and consumer preferences.